How fascism works : the politics of US and them - Stanley, Jason 1969- (Random House, 2020)
The mythic past -- Propaganda -- Anti-intellectual -- Unreality -- Hierarchy -- Victimhood -- Law and order -- Sexual anxiety -- Sodom and Gomorrah -- Arbeit Macht Frei